Contemporary Scales of the Shadow Economy in Kazakhstan - KYDYROVA, Zhamilya; ONLASYNOV, Erlan; SHADIEVA, Aigul; ABDRAKHMANOVA, Akmaral; UMBITALIEV, Altynsary; SEIDAKHMETOV, Marat (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The issues of the general reasons for the existence of the shadow economy and the factors that determined its enormous scale in the contemporary realities of the economic system of Kazakhstan are the subject of consideration of many researchers. However, the authors try to evaluate the results of development programs and the activity of bodies contributing to the modernization of economic policy aimed at structural changes in the policy of counteracting the shadow economy, which have been previously considered ambiguously. The main attention of the authors is given to the study of the phenomenon of ‘shadow economy’ as a special segment of a market economy, as well as to the development of practical recommendations for minimizing the disruptive mechanism’s consequences of shadow activity in the post-socialist period. The impact of the shadow economy on the financial and economic development and security of Kazakhstan are comprehensively studied for understanding the scales of the phenomenon. The authors analyze anthropological factors associated with the contradictory nature of man, economic factors inherent in the market economy and distortions in the state tax policy, insufficient saturation of the market with goods and services, imbalance between various spheres and sectors of the national economy, and low purchasing power of the population. The focus is made on legal factors that have arisen due to the imperfection of the legislative framework and coordination mechanism for combating economic crime, the insufficient activity of law enforcement agencies in the sphere of suppression of illegal and criminal economic activity. The main reasons for the permanent strengthening of shadow activity in the modern economy of Kazakhstan are identified in their direct interrelation with the features of the national model of economic reform. These reasons include: the insecurity of small and medium private property rights from the arbitrariness of the state, the illegal nature of privatization, the dominance of monopolies in the economy and the repressive nature of taxation, etc. These factors have generated not only the traditional shadow activity in Kazakhstan, but the other forms have appeared: labor activity without official registration; manipulations with securities issued by ‘quasi-private’ structures; forceful elimination of competition by regulatory and law enforcement agencies in favor of certain companies and the export of capital from the country according to offshore schemes and technologies, etc. The results of the study on the degree of influence of the features of reforming the Kazakhstani economy on the development of shadow activity make a certain contribution to the study of the phenomenon of the shadow economy in Economic Science. The situation with the spread of the pandemic has once again demonstrated the scale of the shadow economy, the level of corruption of power structures and the steady growth of shadow capital in the country.